You Are Where You Edit: Locating Wikipedia Contributors through Edit Histories - Lieberman, Michael; Lin, Jimmy (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
Whether knowingly or otherwise, Wikipedia contributors reveal their interests and expertise through their contribution patterns. An analysis of Wikipedia edit histories shows that it is often possible to associate contributors with relatively small geographic regions, usually corresponding to where they were born or where they presently live. For many contributors, the geographic coordinates of pages they have edited are tightly clustered. Results suggest that a wealth of information about contributors can be gleaned from edit histories. This illustrates the efﬁcacy of data mining on large, publicly-available datasets and raises potential privacy concerns.